The influence of self-efficacy on sixth graders’ mathematical communication skills - Siti Muhdiati; Dinn Wahyudin; Nurul Umrotullatifah (Inovasi Kurikulum)
Mathematical communication skills are essential for students' success in problem-solving, critical thinking, idea articulation, and addressing challenges. These skills are a key component of 21st-century competencies, supporting mathematical literacy from an early age. This study investigates the effect of self-efficacy on students' confidence in completing academic tasks and the mathematical communication skills of grade VI elementary school students. Using a quantitative approach with an ex post facto method, data were collected via questionnaires to assess self-efficacy and tests to measure mathematical communication skills. The results showed a significant positive effect of self-efficacy on mathematical communication skills, with a significance value and a positive coefficient. The R Square value indicates that self-efficacy accounts for the variance in mathematical communication skills. These findings highlight the critical role of self-efficacy in enabling students to confidently and competently communicate mathematical concepts. To enhance students' mathematical communication skills, teachers should employ learning strategies that build confidence and reinforce self-efficacy. Strengthening self-efficacy boosts academic performance and equips students with the tools to excel in mathematics and related challenges.